Permeability of SPEV Cell Membranes for Water and DMSO Molecules - Kovalenko, I. F.; Koschiy, S. V.; Timofeyeva, E. V.; Sakun, A. V.; Kovalenko, S. Ye.; Vysekantsev, I. P.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2009)
Using the volumetry method there were defined the permeability coefficients of SPEV cell membranes for water and DMSO. It has been established that with increasing the volumes of cell dimensions their membrane permeability for DMSO molecules reduces. Numeric modeling of osmotic behavior of SPEV cells during freezing in DMSO presence has shown that during cooling with 1°C/min the dehydration of SPEV cells occurs within the temperature range of –7.5...–1°C and the rise of cooling rate up to 5°C/min and higher may be the cause of intracellular crystallization.